METHOD OF TREATMENT OF EGFR INHIBITOR TOXICITY (2010)
The invention provides a method of treating and/or preventing a toxicity associated with epidermal growth factor receptor (EGFR) inhibitor therapy in a subject, the method comprising administering to the subject an effective amount of a steroid sulfatase (STS) inhibitor. The toxicity may be ocular toxicity; or dermatologic toxicity, such as papulopustular rash. The EGFR inhibitor may be selected from the group consisting of: a small molecule; an antibody or derivative or fragment thereof; another agent that targets the extracellular or intracellular domain of the EGFR, such as a tyrosine kinase inhibitor selected from the group consisting of: erlotinib; gefitinib; lapatinib; and any combination thereof. The EGFR inhibitor may also be antibody selected from the group consisting of: cetuximab; panitumumab; and any combination thereof.Preferably the STS inhibitor is selected from the group consisting of: alternative STS substrates; reversible STS inhibitors; and irreversible STS inhibitors; and any combination thereof. A preferred STS inhibitor is the irreversible nonsteroidal STS inhibitor STX64.In some embodiments, the subject receiving EGFRI therapy has a cancer comprising cells that express wildtype k-ras and/or wildtype b-raf. In other embodiments, the cancer may be hormone-dependent. Cancers that may be treated with EGFRI therapy include colorectal cancer and non-small cell lung cancer.